What is A Network? (And Who is Andrew Lang?) - Hensley, Nathan (Romanticism and Victorianism on the Net, 2013)
This essay traces the strikingly prolific career of Andrew Lang and places that career in the context of the shifting late-Victorian literary field, which Lang served importantly to shape. The essay introduces Lang’s milieu and re-orients readers to a literary personality who, while known, is only rarely studied in his own right—a detail of reception history the essay explains with recourse to the relational sociology of Pierre Bourdieu and Bruno Latour. Restoring Lang’s “network effect” through historical analysis helps raise a number of conceptual questions, each of which is pursued in the essays of this special issue: such questions include the nature of textual interpretation, the changing outlines of disciplines, the philosophy of historical method, and conceptions of authorship and collaboration in the modern cultural marketplace. Placing Lang back in his proper spot at the center of the late-Victorian networks he helped convene (1) helps historicize our understanding of the modern “field of cultural production” (Bourdieu’s term) in an expanded, protodisciplinary sense and (2) discloses new genealogies of literary and theoretical history. These new genealogies in turn cast altered light on the methodological presuppositions we draw upon to evaluate Lang and his network here. “Theoretical historicism” is the term used to describe approaches that trace such feedback loops between the historical object analyzed and the modern method used to analyze them.